The microscopic determination of age in cattle bone fragments (Bos taurus L.) - Hincak, Zdravka; Mihelić, Damir; Kuzmanović, Željka; Durman, Aleksandar (2008)
Microscopic analysis closely examines one hundred and fifty (150) femoral bone fragments of cattle (Bos taurus, L.). Each fragment was of known age. Samples originate from grown-up cattle and were divided into three groups according to age ranges. Fragments from the mid-shaft of fresh femoral bone were prepared for histological thin-section analysis according to the protocol. Age related changes include changes in number of osteon systems and percentage of lamellar and plexiform bone tissue. This analysis could be a contribution to a classical macroscopic method for age determination of cattle bone fragments in archaeozoology or veterinary forensic sciences.
Projekt MZOS
ENG